The Comparison in the Microstructure and Mechanical Properties between AZ91 Alloy and Nano-SiCp/AZ91 Composite Processed by Multi-Pass Forging Under Varying Passes and Temperatures - K.B. Nie (Materials, 2019)
In this study, both AZ91 alloy and nano-SiCp/AZ91 composite were subjected to multi-pass forging under varying passes and temperatures. The microstructure and mechanical properties of the alloy were compared with its composite. After six passes of multi-pass forging at a constant temperature of 400 ℃, complete recrystallization occurred in both the AZ91 alloy and composite. The decrease of temperature and the increase of passes for the multi-pass forging led to further refinement of dynamic recrystallized grains and dynamic precipitation of second phases. The grain size of the nano-SiCp/AZ91 composite was smaller than that of the AZ91 alloy under the same multi-pass forging condition, which indicated that the addition of SiC nanoparticles were beneficial to grain refinement by pinning the grain boundaries. The texture intensity for the 12 passes of multi-pass forging with varying temperatures was increased compared with that after nine passes. The ultimate tensile strength is slightly decreased while the yield strength was increased unobviously for the AZ91 alloy with the decrease of temperature and the increase of the passes for the multi-pass forging. Under the same condition of multi-pass forging, the yield strength of the composite was higher than that of the AZ91 alloy due to the Orowan strengthening effect and grain refinement strengthening resulting from externally applied SiC nanoparticles and internally precipitated second phases. By comparing the microstructure and mechanical properties between the AZ91 alloy and nano-SiCp/AZ91 composite, the strength-toughness properties of the composites at room temperature were affected by the matrix grain size, texture evolution, SiC nanoparticles distribution and the precipitated second phases.